A Core Curriculum for Postgraduate Program in Nonsurgical Aesthetics: A Cross-sectional Delphi Study. (11th April 2022) - Kumar, Narendra; Parsa, Ali Davod; Rahman, Eqram
Abstract: Background: The desire for portraying a young and beautiful face and body is driving people to seek aesthetic treatment and accelerating the exponential growth of nonsurgical aesthetic (NSA) procedures. Unfortunately, despite impressive advances, NSA is yet to have a formal clinical education program. Objectives: This study aimed to identify the content and structure of an evidence-based postgraduate curriculum in NSA. Methods: The Delphi questionnaire was developed after a comprehensive literature review and a focus group discussion. The questionnaire was emailed to 40 experts and 20 trainee physicians worldwide through the online survey platform and was asked to assign a rating on a 4-point Likert scale. A "1" represents a strong disagreement about integrating a topic in the NSA curriculum, and a "4" indicates a firm agreement. A pre-fixed percentage agreement of 80% and Cronbach's α = 0.90 was established to represent a consensus for the current study. Results: The response rate for the Delphi study was 90.0%, 88.8%, and 90% in the first, second, and third rounds, respectively. The experts and trainee physicians agreed with all the proposed topics (≥80%) and considered them critical for the proposed NSA curriculum. The mean score for each was ≥ 3, and Cronbach's α value for the Delphi was 0.94, confirming internal consistency and reliability. Conclusions: The consensus demonstrates significant advances toward developing an evidence-based curriculum for a postgraduate program in NSA, which is essential to support the growing demand for trained aesthetic physicians.